Overall Stability Analysis of Xiluodu High Arch Dam Based on Fine Three-Dimension Numerical Modeling - Tianhui Ma; Zhiqiang Feng; Chun'an Tang; Peng Lin; Kedar Prasad Yadav (Advances in Civil Engineering)
The RFPA3D is used to establish a fine finite element model of 6.63 million elements, which realizes the fine simulation of the stability of the Xiluodu arch dam under layered, overall, multiworking conditions and multistress fields, and the cracking and failure process under overload. The structural design scheme of the arch dam and the corresponding foundation treatment design are evaluated. The model fully reflects the measures of dam shape structure design, angle fitting structure design, and foundation concrete replacement in the Xiluodu arch dam technical design stage. The RFPA3D adopts the mesoelement elastic damage model, which considers the Mohr–Coulomb criterion of shear fracture and the maximum tensile failure criterion, and assumes that the mechanical properties of the element satisfy Weibull distribution to consider its heterogeneity. The simulation results show that, under normal load conditions, the dam foundation surface after comprehensive reinforcement has better overall stability, the stress and deformation of the dam body have good symmetry, and the overload factor of crack initiation under overload calculation K1 = 2P0 (P0 is normal water load), the nonlinear deformation overload factor K2 = 3.5–4P0, and the limit load factor K3 = 7.5–8.0P0, dam safety can be satisfied. The RFPA3D is used to establish a superlarge fine model to study the overall stability of the high arch dam, which provides an effective method for analysis and research of other large hydraulic projects in the world.